Indicators of manifestations of deviant behavior of young athletes in the process of training activity - Skok, N. S.; Makarov, Yu. M.; Kulikov, V. S.; Lutkova, N. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the causes and types of manifestations of deviant behavior of young athletes in the process of training activities based on the results of an expert survey.